Notions of law, citizenship and democracy in Brazilian school curriculum: for a new teaching practice (Research, Society and Development, 2019)
Currently, it is necessary to readjust curricular and teaching practices in order to encourage the formation of the citizen in elementary school students school students. Thus, basic notions of law, constitutional principles and rights and obligations within society become imperative for the construction of a citizen with a critical and politicized mind. In this way, the aim is to demonstrate the importance of the theme and the means to carry out this construction.  It is understood that by providing such knowledge in the school curriculum, the student will be able to understand the social and economic situation of Brazil and be able to analyze more adequately the political structure of the country, ruled by democracy. Thus, the relevance of curricular re-adaptation is highlighted, providing notions of law and citizenship in schools.